Ways to improve power quality under the conditions of industrial enterprises - Kuznetsov, V.; Kuznetsova, A.; Tryputen, M. (НТУ ДП, 2021)
Wide experience has been accumulated by now in the field of research concerning power quality effect on the operation of cage-rotor asynchronous motors. For instance, while studying the problems, connected with qualitative estimation of damage by the abovementioned electromechanical converters operating under the conditions of supply voltage asymmetry, authors of paper [1] have concluded that at 2Uk =3.5% value, motor winding temperature increases by 25%. Paper [2] has determined that operation life of an asynchronous motor halves, if voltage unbalance ratio increases by 4% in terms of negative 2Uk sequence.
Keywords: improve power; industrial enterprises